Liver Transplantation for Hepatitis C and Alcoholic Liver Disease - Marco Carbone; James Neuberger (Journal of Transplantation)
End-stage liver disease due to hepatitis C (HCV) and cirrhosis from alcohol (ALD) are the commonest indications for liver transplantation in the western countries. Up to one third of HCV-infected transplant candidates have a history of significant alcohol intake prior to transplantation. However, there are few data available about the possible interaction between alcohol and HCV in the post-transplant setting. Patients with both HCV and alcohol are more likely to die on the waiting list than those with ALD and HCV alone. However, after transplantation, non-risk adjusted graft and patient survival of patients with HCV + ALD are comparable to those of patients with HCV cirrhosis or ALD cirrhosis alone. In the short and medium term HCV recurrence after transplant in patients with HCV + ALD cirrhosis does not seem more aggressive than that in patients with HCV cirrhosis alone. A relapse in alcohol consumption in patients with HCV + ALD cirrhosis does not have a major impact on graft survival. The evidence shows that, as is currently practiced, HCV + ALD as an appropriate indication for liver transplantation. However, these data are based on retrospective analyses with relatively short follow-up so the conclusions must be treated with caution.